DOIMIY MAGNITNING MAGNIT MAYDON INDUKSIYASINI ANIQLASH USULLARI VA UNI AMPER QONUNI YORDAMIDA ANIQLASH METODIKASI - Xolboyev, Yu.X. (SCIENCE and SOCIETY, 2024)
In this article, the fields of application of permanent magnet and current methods of analysis of permanent magnetic field induction are analyzed, checked and verified documents. Here is a practical experimental method for determining the induction of a permanent magnetic field close to Ampere's law. Based on the obtained sources, create important information about the application of experimental devices to production.
Keywords: permanent magnet; magnetic field; magnetic field induction; Ampere's law; earth's magnetic field